2011
DOI: 10.1158/0008-5472.can-10-3382
|View full text |Cite
|
Sign up to set email alerts
|

β2-Microglobulin Induces Epithelial to Mesenchymal Transition and Confers Cancer Lethality and Bone Metastasis in Human Cancer Cells

Abstract: Bone metastasis is one of the predominant causes of cancer lethality. This study demonstrates for the first time how β2-microglobulin (β2-M) supports lethal metastasis in vivo in human prostate, breast, lung and renal cancer cells. β2-M mediates this process by activating epithelial to mesenchymal transition (EMT) to promote lethal bone and soft tissue metastases in host mice. β2-M interacts with its receptor, hemochromatosis (HFE) protein, to modulate iron responsive pathways in cancer cells. Inhibition of ei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 37 publications
1
136
0
3
Order By: Relevance
“…Upon exposure to certain soluble factors or host bone microenvironment, low-invasive and epithelial-like ARCaP E cells undergo EMT and acquire invasive properties (26,27). Western blot analysis showed that both EGFR and neu (HER2/ ErbB2) were highly expressed and phosphorylated in ARCaP E cells and their highly metastatic, mesenchymal-like counterparts ARCaP M cells (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Upon exposure to certain soluble factors or host bone microenvironment, low-invasive and epithelial-like ARCaP E cells undergo EMT and acquire invasive properties (26,27). Western blot analysis showed that both EGFR and neu (HER2/ ErbB2) were highly expressed and phosphorylated in ARCaP E cells and their highly metastatic, mesenchymal-like counterparts ARCaP M cells (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Although it is generally accepted that the immune system plays a role in PCa, the exact mechanism by which the immune system is involved in PCa initiation, progression and treatment remains unclear. 41,44 Sipuleucel-T has been approved by the US FDA as a cellular immunotherapy that improves overall survival in asymptomatic or minimally symptomatic metastatic castrate-resistant PCa patients, and other immunotherapies such as ipilimumab are in advanced stages of clinical development. 45,46 However, some have doubted its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-m/HFE complex protects against the influx and accumulation of intracellular iron and negatively regulates intracellular iron concentration in cancer cells, mediated by 2-m/HFE complex interaction with transferrin receptor (TFR) [38,39]. We also found that lower levels of intracellular iron concentration caused by the 2-m/HFE complex activate hypoxia inducible factor-1 (HIF-1 ) and induce overexpression of its downstream target genes in cancer cells, driving EMT and promoting cancer lethal bone and soft tissue metastases [34]. This cell signaling network is highly conserved in human prostate, kidney, lung, and breast cancer cells, with activation of 2-m/HFE complex resulting in the induction of EMT, the lethal progression of these cancers to host bone and soft tissues and ultimately the demise of the host.…”
Section: Introductionmentioning
confidence: 85%
“…We reported that 2-m played multiple roles in cancer development and mediates tumorigenesis, angiogenesis, and osteomimicry [30,31,34]. 2-m is also known to promote the growth and survival of stromal cells, such as mesenchymal stem cells (MSCs), osteoblasts, and osteoclasts supporting cancer bone metastasis [31,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation